A critical friendship : Donald Justice and Richard Stern, 1946-1961 - Justice, Donald, 1925-2004; Stern, Richard, 1928-2013; Murphy, Elizabeth, 1983- (University of Nebraska Press, 2013)
"A chance meeting in the University of North Carolina campus library in 1944 became the beginning of a decades-long friendship and sixty-year correspondence. Donald Justice (1925-2004) and Richard Stern (1928-2013) would go on to become, respectively, the Pulitzer Prize-winning poet and the acclaimed novelist. A Critical Friendship showcases a selection of their letters and postcards from the first fifteen years of their correspondence, representing the formative period in both writers' careers. It includes some of Justice's unpublished poetry and early drafts of later published poems as well as some early, never-before-published poetry by Stern. A Critical Friendship is the story of two writers inventing themselves, beginning with the earliest extant letters and ending with those just following their first major publications, Justice's poetry collection The Summer Anniversaries and Stern's novel Golk. These letters highlight their willingness to give and take criticism and document the birth of two distinct and important American literary lives. The letters similarly document the influence of teachers, friends, and contemporaries, including Saul Bellow, John Berryman, Edgar Bowers, Robert Lowell, Norman Mailer, Allen Tate, Peter Hillsman Taylor, Robert Penn Warren, Eudora Welty, and Yvor Winters, all of whom feature in the pair's conversations. In a broader context, their correspondence sheds light on the development of the mid-twentieth-century American literary scene. "--